Mexican species of the genus Probles Förster (Hymenoptera: Ichneumonidae: Tersilochinae) - Khalaim, Andrey I.; Ruíz-Cancino, Enrique (Zootaxa, 2019)
Mexican species of the genus Probles Förster are reviewed. Twelve species have been discovered from Mexico, all belong to the subgenus Euporizon Horstmann and are new to science: P. alejandroi Khalaim, sp. nov., P. belokobylskii Khalaim, sp. nov., P. clypeola Khalaim, sp. nov., P. contrerasi Khalaim, sp. nov., P. juanitae Khalaim & Ruíz-Cancino, sp. nov., P. lunai Khalaim, sp. nov., P. megasoma Khalaim & Ruíz-Cancino, sp. nov., P. miquihuana Khalaim & Ruíz-Cancino, sp. nov., P. picus Khalaim & Ruíz-Cancino, sp. nov., P. spectabilis Khalaim & Ruíz-Cancino, sp. nov., P. xalapana Khalaim, sp. nov. and P. zacapoaxtlana Khalaim, sp. nov. One species, P. megasoma sp. nov., is also recorded from Costa Rica. An identification key to species of Probles occurring in Mexico is given.